Estimates for bilinear approximations of the classes TeX of periodic functions of two variables - Solich, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain exact-order estimates for the best bilinear approximations of the classes S_p, θ^Ω B of periodic functions of two variables in the space L_q for some relations between the parameters p, q, θ.